Diseño y construcción de un sistema de bombeo mediante rueda hidráulica de alimentación inferior, para la granja de pollos avícola serrano. - Vaca Ludeña, Rolando Efraín (2014)
In the present work, it is exposed the design and construction of a pumping system through a waterwheel of lower feed for an agricultural farm in the Loja province, Gonzanamá canton, and Santa Rita neighborhood. The design and construction of this system were done based on the hydraulic potential of a water channel from the place, and the needs of the farm. This system consists of two main components, a water wheel and a piston pump, as well as other necessary elements for its operation such as: chain drive, bearings, pipe and hydraulic accessory. The operation of the system is by the process of energy transformation, the waterwheel capture the kinetic energy of the water flow through its blades, causing the rotation thereof and a torque due to the power, which is transmitted to the shaft of the piston pump via a chain drive system for pumping water. Also, it was studied in detail its performance under conditions of variable work, where the waterwheel reached an efficiency of up to 68.6% and the pump 96.9%. The overall pumping system implemented achieves an efficiency of up to 64.5 %. The use of this system is a good alternative to mitigate the effects by the use of pollutants pumping systems, being that, it is sustainable and friendly system with the environment.